Celiac disease in a large cohort of children and adolescents with recurrent headache: A retrospective study. Issue 5 (May 2016) - Nenna, Raffaella; Petrarca, Laura; Verdecchia, Paola; Florio, Matteo; Pietropaoli, Nicoletta; Mastrogiorgio, Gerarda; Bavastrelli, Maria; Bonamico, Margherita; Cucchiara, Salvatore
Abstract: Background: The clinical picture of celiac disease is changing with the emergence of subclinical forms and growing evidence reporting associated neurological disorders. Aims: To establish the prevalence of celiac disease in children suffering from recurrent headache. Methods: In our retrospective study we collected charts from 1131 children attending our tertiary care Centre for Paediatric Headache over the period 2001–2012. They were screened for celiac disease and positive patients were referred to our Operative Unit for Coeliac disease and confirmed positive children underwent upper endoscopy with multiple duodenal biopsies. Celiac children started a gluten-free diet. Results: 883 children (481 females; median age, 9.8 years, range 3–19) performed celiac disease screening, and among them, 11 children (7 females; median age, 8.2 years, range: 4.8–13.9) were diagnosed with celiac disease. Seven children (5 females, median age, 11.9 years, range: 10.3–13.9) had been diagnosed as celiac prior to the neurological evaluation. The prevalence of celiac disease in our sample is 2.04% vs. 1.2% of the general population ( p = 0.034). Conclusions: Our study demonstrates, on a large series, that celiac disease prevalence is doubled in patients with chronic headache. Screening for celiac disease could be advised as part of the diagnostic work-up in these paediatric patients, particularly among pharmacological non-responders.